Implementasi Mobile Homecare Berbasis User Centered Desain (UCD) - I Made Bayu Sastra Wiguna; Ketut Agus Suputra; Agus Aan Jiwa Permana (MASALIQ, 2026)
Homecare services have become an important alternative in healthcare delivery because they allow patients to receive medical care directly at home with a higher level of comfort. However, the use of web-based homecare services still faces limitations when accessed via mobile devices, particularly in terms of usability and accessibility. This study aimed to develop a mobile-based homecare platform that focuses on enhancing user experience through a User-Centered Design (UCD) approach. A Research and Development (R&D) method was employed, following UCD stages that include understanding the context of use, identifying user needs, designing solutions, and evaluating the design. The application was developed using Flutter for the frontend and Laravel for the backend with a REST API architecture. Usability evaluation was conducted using the System Usability Scale (SUS) method involving 20 respondents. The evaluation results showed that the developed application obtained a SUS score of 86, which falls into the good usability category, indicating that the application is easy to use and well accepted by users. The application improves users’ ease of accessing homecare services and obtaining real-time service information. This study is expected to provide a practical solution for developing mobile-based healthcare applications and to serve as a reference for future research on usability and the application of User-Centered Design.